2001
DOI: 10.1183/09031936.01.17304560
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a simplified oscillation technique for assessing airway obstruction in sleep apnoea

Abstract: The forced oscillation technique (FOT) is a noninvasive method that is useful for assessing airway obstruction and for titrating continuous positive airway pressure (CPAP) in patients with sleep apnoea. The aim was to evaluate the routine applicability of a simpli®ed FOT set-up based on recording pressure and¯ow at the level of the CPAP device, i.e. obviating the need for connecting the transducers to the nasal mask.A correction to account for the tubing and the exhaust port was applied. This simpli®ed FOT was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…The FOT-derived impedance |Z| signal has previously been used to identify upper airway obstruction during sleep in OSA [17]. Upper airway closure is a dynamic process in OSA associated with an instantaneous large increase in respiratory resistance, which cannot be accounted for by other changes within the respiratory system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The FOT-derived impedance |Z| signal has previously been used to identify upper airway obstruction during sleep in OSA [17]. Upper airway closure is a dynamic process in OSA associated with an instantaneous large increase in respiratory resistance, which cannot be accounted for by other changes within the respiratory system.…”
Section: Discussionmentioning
confidence: 99%
“…Oscillatory impedance measured using the FOT FOT was applied as previously described [17,18,25]. A fullface mask was connected to a mesh wire-based pneumotachograph (resistance50.522 L?s ) through all the tubing was applied to the system in order to avoid rebreathing.…”
Section: Polysomnographymentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, only one false-negative misclassification out of the 372 analysed breaths was found, suggesting that leakages may have negligible effects on the detection of EFL by FOT. Moreover, as the pneumotachograph can easily measure leakages [20], the presence of abnormally large leaks can be automatically identified, to indicate the possible loss of reliability in detecting EFL.…”
Section: Automatic Detection Of Efl During Cpapmentioning
confidence: 99%